Heat transfer augmentation in a circular tube using V-nozzle turbulator inserts and snail entry - Promvonge, Pongjet; Eiamsa-ard, Smith (My University, 2007)
Influences of V-nozzle turbulator inserts in conjunction with a snail entry on heat transfer and friction loss characteristics in a circular tube are experimentally investigated in this paper. In the present work, a set of converging-diverging nozzles like a venturi structure (referred to as V-nozzle) used as a turbulator/reverse-flow generator is placed inside the test tube through which air as the test fluid is passed. Also, the snail is mounted at the tube entrance to create a decaying swirl flow. The effects of the snail entry and insertion of V-nozzles with three different pitch ratios, PR = 2.0, 4.0, and 7.0 on heat transfer rate in the tube are examined for the Reynolds number ranging from 8000 to 18,000. The experimental results are displayed in terms of Nusselt number (Nu) and friction factor (f) as a function of Reynolds number (Re). The values of Nusselt number and friction factor for utilizing both the V-nozzle and the snail entry are found to be considerably higher than that for using the V-nozzle alone or the plain tube. The use of PR = 2.0 leads to higher Nusselt number and friction factor values than that of PR = 4.0 or 7.0. To assess the real benefits in using the turbulator and the swirl generator of the enhanced tube, empirical correlations in terms of Re and PR for Nusselt number, friction factor and performance evaluation criteria are also determined. © 2007 Elsevier Inc. All rights reserved.
Keywords: Heat transfer enhancement; Pitch ratio (PR=1 + S); Reverse flow; Snail; Swirl flow; Turbulator; V-nozzle